Monumentaliser ou dé-monumentaliser les habitants du passé par la représentation ? Entre acte mémoriel et spectralité : les Stolpersteine de Gunter Demnig - Dominique Trouche (Les Cahiers de Framespa)
The artistic work Stolpersteine created by Gunter Demnig consists of pavements covered with brass put in the entrance of place of victims’ house of the National Socialism. Quite at the same time artistic and memory act, this project, which exists since 1993 (date of creation), knows since the beginning of 2000s a very strong expansion in Europe. Visible and invisible work (it is pavements put on the ground of cities and that are not indicated) and work which re-territorializes the victims by linking them with their last known address, Stolpersteine summon the inhabitant of past and updates a superimposing past-present, thus tending to cause forms of revenance or spectrality. Also by its essence and its rhetoric, the work contains quite at the same time a monumental dimension and a none monumental dimension.